"No-Touch" versus "Endo" Vein Harvest: Early Patency on Symptom-Directed Catheterization and Harvest Site Complications. Issue 4 (July 2014) - Mannion, John D.; Marelli, Daniel; Brandt, Todd; Stallings, Megan; Cirks, Jeffery; Dreifaldt, Mats; Souza, Domingos
Objective: "No-touch" (NT) saphenous vein harvesting preserves the adventitial vasa vasorum, prevents medial ischemia, and is associated with an improved short-term and long-term vein graft patency. It may also be associated with a higher rate of harvest site complications. Endovascular vein harvesting (endo-vein) has a low rate of harvest site complications but also a tendency toward a lower patency rate. Methods: During a 2-year period (2011–2012), we compared the vein graft patency at symptom-directed cardiac catheterization as well as wound complication rates in 210 patients who received either NT (87 patients) or endo-vein (123 patients). Results: The recatheterization rate for the two groups was similar: 9 (10.3%) of 87 of the NT patients versus 11 (9.0%) of 123 of the endo-vein patients. There was a significant difference in vein graft patency between the groups: 15 (94%) of 16 NT vein grafts were patent versus 6 (27%) of 22 of endo-veins ( P < 0.02). The endo-vein graft patency during this 2-year period was similar to the total endo-vein patency (37%) during a 4-year period. A comparison between a more experienced and a less experienced harvester revealed no difference in patency rate. Harvest site complications were significantly higher with the NT harvest: 18% of the NT patients requiring vacuum-assisted wound closure or intravenous antibiotics versus 2% of the endo-vein patients ( P < 0.0001). The application of platelet-rich plasma did not significantly lower wound complication rates ( P = 0.27). Conclusions: These results suggest that NT vein harvesting may be associated with improved graft patency, but methods should be developed to lower wound complication rates.